2021
DOI: 10.1136/jitc-2021-003277
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of vedolizumab and infliximab treatment for immune-mediated diarrhea and colitis in patients with cancer: a two-center observational study

Abstract: BackgroundCurrent treatment guidelines for immune-mediated diarrhea and colitis (IMDC) recommend steroids as first-line therapy, followed by selective immunosuppressive therapy (SIT) (infliximab or vedolizumab) for refractory cases. We aimed to compare the efficacy of these two SITs and their impact on cancer outcomes.MethodsWe performed a two-center, retrospective observational cohort study of patients with IMDC who received SITs following steroids from 2016 to 2020. Patients’ demographic, clinical, and overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 35 publications
6
72
0
Order By: Relevance
“…Along these lines, a retrospective study of 184 patients with ICI-colitis that compared patients treated with infliximab, a TNFi, to vedolizumab, which targets integrin α 4 β 7 and prevents gut but not systemic inflammation, showed infliximab to be associated with a higher rate of cancer progression. 72 …”
Section: Ici-arthritis Managementmentioning
confidence: 99%
“…Along these lines, a retrospective study of 184 patients with ICI-colitis that compared patients treated with infliximab, a TNFi, to vedolizumab, which targets integrin α 4 β 7 and prevents gut but not systemic inflammation, showed infliximab to be associated with a higher rate of cancer progression. 72 …”
Section: Ici-arthritis Managementmentioning
confidence: 99%
“…Other studies have shown that vedolizumab is associated with a clinical response rate of 95% in patients with ICI-induced colitis who did not receive prior infliximab, with an endoscopic remission rate > 50% [ 30 ]. The vedolizumab-alone group had the lowest rate of colitis recurrence compared with the infliximab-alone group, and patients received combined selective immunosuppressive therapies sequentially [ 31 ]. It might be better to switch to vedolizumab treatment in recurrent refractory cases against infliximab.…”
Section: Discussionmentioning
confidence: 99%
“…Vedolizumab is a humanized monoclonal antibody used to treat ulcerative colitis, which acts by binding to α4β7 integrin on T lymphocytes, thereby reducing lymphocyte trafficking to the gut. In a retrospective study of 184 patients with cancer and immune-mediated diarrhea and colitis (IMDC), treatment with vedolizumab led to a similar IMDC response rate as infliximab treatment [ 37 ]. However.…”
Section: Could Corticosteroids Used For the Management Of Side Effect...mentioning
confidence: 99%